2015
DOI: 10.3346/jkms.2015.30.12.1815
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features of Drug-induced Liver Injury According to Etiology

Abstract: Drug-induced liver injury (DILI) is an increasingly common cause of acute hepatitis. We examined clinical features and types of liver injury of 65 affected patients who underwent liver biopsy according DILI etiology. The major causes of DILI were the use of herbal medications (43.2%), prescribed medications (21.6%), and traditional therapeutic preparations and dietary supplements (35%). DILI from herbal medications, traditional therapeutic preparations, and dietary supplements was associated with higher elevat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 15 publications
2
10
0
1
Order By: Relevance
“…In most of these liver injury studies, HILI cases were less frequently observed as compared to DILI cases. 1 , 27 29 This discrepancy is best explained by a higher use of synthetic drugs, as compared to herbal products, among the assessed cohorts.…”
Section: Epidemiology Of Overall Liver Injury Casesmentioning
confidence: 96%
See 1 more Smart Citation
“…In most of these liver injury studies, HILI cases were less frequently observed as compared to DILI cases. 1 , 27 29 This discrepancy is best explained by a higher use of synthetic drugs, as compared to herbal products, among the assessed cohorts.…”
Section: Epidemiology Of Overall Liver Injury Casesmentioning
confidence: 96%
“… 28 In a single-center retrospective analysis from Korea during 2003 to 2013, the major causative agents among the DILI/HILI cohort were HMs (43.1%), prescription medications (21.6%), and traditional therapeutic preparations or dietary supplements (35%). 29 Among 899 DILI/HILI patients in a study from the United States, 145 patients (16.1%) with liver injury were associated with the use of HDSs. 30 , 31 In a retrospective analysis of a liver injury cohort consisting of 1,985 DILI/HILI patients from the Military Hospital in Beijing between 2009 and 2014, 563 patients (28.4%) were diagnosed with HILI caused by herbal TCMs.…”
Section: Epidemiology Of Overall Liver Injury Casesmentioning
confidence: 99%
“…De Ritis, et al indicated that abnormally elevated levels of ALT and AST combined with AST/ALT ratio could be a sensitive index of an activity of a liver disease [21]. Lower AST/ALT ratios were found in viral hepatitis [21][22][23][24], drug-induced liver injury [25,26], and metabolic syndrome [27], but higher AST/ALT ratios were found in cholestasis [21], nonalcoholic fatty liver disorder [23], liver cirrhosis [22,24,28], and even alcoholic liver disorder [23,24,29]. For carbon tetrachloride-induced hepatotoxicity, the AST/ALT ratio decreased (1.09−1.16) while compared with control group (1.79−1.88) [19,20], and so did it in the study (1.25).…”
Section: Discussionmentioning
confidence: 99%
“…The ingredients of prescription drugs are generally known, while the exact causative ingredients among the herbs and folk remedies used in traditional medicine remain unclear [49]. Similar with prescription medications, the liver injury type observed among herbal and dietary supplements is predominantly hepatocellular too [50]. Thus, the -values based methodologies for DILI classification might not be an appropriate approach for Asian patients as compared with the patients in Western countries.…”
Section: Clinical Features Of Dili/hilimentioning
confidence: 98%